Comparative leaf, root morpho-anatomical phenes in sugarcane wild germplasm and commercial genotypes conferring drought and salinity stress tolerance - P.Vinoth; G. Ariharasutharsan; A. Malarvizhi; P. Senthilrajan; C. Appunu; V.Vinu; H.K.MAHADEVA Swamy; R, Valarmathi (Journal of Sugarcane Research, 2024)
The morpho-anatomical phenes which plays an important role in imparting stress tolerance are less explored for their stress adaptability in sugarcane. The present study was carried out to identify the leaf and root anatomical modifications conferring drought and salinity tolerance in sugarcane germplasm compared to commercial genotypes at early stages of stress development. In the study the commercial hybrids (Co 99004 and Co 86032) showed early physiological stress symptoms with few anatomical modifications viz., cell wall lignification around the metaxylem and reduction in metaxylem diameter elements under both drought and salinity stress. Both the Erianthus clones (SES 347 and SES181) showed several anatomical modifications viz., significantly lignified cells around leaf and root vascular tissues, pericycle, narrowed root metaxylem diameter under drought and salinity stress condition. Erianthus clones showed higher root penetration ability under drought stress with significant anatomical variations viz., smaller cortical cell file, multilayered epidermis and lignified sclerenchymatous hypodermis, lignified endodermis, reduced stele diameter, lignified cells around metaxylem and narrowed metaxylem contributing to root mechanical strength. The study shows that both Erianthus and commercial genotypes could sense the early stage of stress development. At early stages of drought and salinity stress the commercial genotypes were able to survive with few anatomical modifications, while Erianthus clones showed several anatomical modifications to combat the extreme environment. The anatomical traits observed in germplasm clones under salinity and drought stress can be further explored in order to utilize them for developing extreme abiotic stress tolerant sugarcane genotypes.